A case study of quality evaluation from consumers’ perspectives on Malaysian B2C e-commerce websites - Abd Wahab, Alawiyah; Ahmad, Faudziah; Baharom, Fauziah; Yahaya, Jamaiah (Taylor & Francis Group, 2014)
Many researchers have reported that more than seventy five percent of dot.com companies do not last longer than two years.One contributing factor is the ignorance of dot.com companies on the consumer needs in their website development.Furthermore, consumers' perspectives are often ignored e-commerce website evaluations.This paper presents a framework for e-commerce quality and evaluation based on consumer perspectives.The framework consists of four components:e-commerce quality metrics, assessment entity, assessment specification and quality level, In order to illustrate the practicality of the framework, a case study on six Malaysian B2C e-commerce websites has been conducted.The findings show the frame- work is applicable and realistic.The successful implementation of the framework shows that it offers a guidance and standard procedure for e-commmerce website quality evaluation that can be used to improve organization website to meet the consumer need and to keep the organization competitive and sustainable.